2021
DOI: 10.3390/app11135958
|View full text |Cite
|
Sign up to set email alerts
|

Fischer-Tropsch Diesel and Biofuels Exergy and Energy Analysis for Low Emissions Vehicles

Abstract: This research investigates the effects of a synthetic diesel-like fuel (Fischer-Tropsch diesel) and biofuels (ethanol and biodiesel) fuel blends on the energy-exergy efficiencies and gaseous exhaust emissions characteristics of a compression ignition engine. Two blends of alternative fuels denoted as E15B35FTD50 (15% ethanol, 35% biodiesel, and 50% Fischer-Tropsch diesel) and E15B35D50 (15% ethanol, 35% biodiesel, and 50% diesel) were experimentally studied on a single-cylinder diesel engine and compared to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Miyamoto et al [27] has found that for diesel fuels with a low C/H ratio, a lower adiabatic temperature is reached, which can reduce the production of NOx. Since F-T products are synthesised to have almost no aromatics, NOx emissions are expected to be even lower [28,29]. This is supported by Szybist et al [30] who show NOx emissions to be reduced by 21-22% compared to conventional diesel.…”
Section: Fischer-tropsch Synthesismentioning
confidence: 90%
“…Miyamoto et al [27] has found that for diesel fuels with a low C/H ratio, a lower adiabatic temperature is reached, which can reduce the production of NOx. Since F-T products are synthesised to have almost no aromatics, NOx emissions are expected to be even lower [28,29]. This is supported by Szybist et al [30] who show NOx emissions to be reduced by 21-22% compared to conventional diesel.…”
Section: Fischer-tropsch Synthesismentioning
confidence: 90%
“…%). The paraffinic composition of the two fuel fractions (as detailed in the Supplementary Materials, Table S3, streams 20 and 21) was based on relevant literature studies focusing on the production of jet-like and diesel-like fuels from hydrotreated oils [31][32][33]. The simulated jet and diesel fuels resulted in Lower Heating Values (LHVs) of 44.4 MJ/kg and 43.8 MJ/kg, respectively.…”
Section: Tags Hydrotreatmentmentioning
confidence: 99%
“…The importance of electric vehicles for the reduction of GHG emissions and, consequently, lower consumption of oil-based fuels, is indisputable. However, internal combustion engines are still the main form of propulsion in road transportation today and the scenario indicates that they will be used on a large scale for the next decades [1,2].…”
Section: Introductionmentioning
confidence: 99%